Factors Associated with Colostrum Quality and Effects on Serum Gamma Globulin Concentrations of Calves in Swiss Dairy Herds. (23rd August 2017) - Reschke, C.; Schelling, E.; Michel, A.; Remy‐Wohlfender, F.; Meylan, M.
Abstract : Background: Previous studies have shown a high prevalence of failure of passive transfer of immunity (FPT) in Swiss dairy calves. Objectives: To investigate risk factors associated with poor colostrum quality and FPT on Swiss dairy farms. Animals: Colostrum and serum samples from 373 dam‐calf pairs at 141 farms. Methods: The gamma globulin (Gg) concentrations of the dams' colostrum and the calves' serum samples were determined by electrophoresis. Potential risk factors were assessed by logistic regression of questionnaire data. Results: Prevalence values of 15.5% (95% confidence interval [CI], 12.0–19.6%) for low‐quality colostrum (<50 g Gg/L) in cows and 43.5% (95% CI, 38.4–48.8%) for FPT (serum Gg < 10 g/L) in calves were estimated. The main factors associated with low colostrum quality included colostrum leakage before or during parturition and a time lag > 6 hours between parturition and first milking. The results confirm that the occurrence of FPT in calves primarily was influenced by the quality of colostrum, the amount of ingested colostrum, and the time between birth and first feeding. Conclusions and Clinical Importance: These results confirm a large potential for improvement in colostrum harvesting and colostrum feeding procedures in the study herds. Control for colostrum leaking intra‐partum, early colostrum milking, and ensuring that the calves ingest a sufficient volume of colostrum within the first hours of life are measures that can be readily implemented by farmers to decrease the incidence of FPT without additional workload.